Women and leadership : journey toward equity - DeFrank-Cole, Lisa; Tan, Sherylle J. (Thousand Oaks : SAGE Publications, Inc., 2022)
While women in the United States account for nearly half the workforce, they continue to encounter unique personal, social, and structural dynamics as leaders. Authors Lisa DeFrank Cole and Sherylle J. Tan explore these dynamics and more in Women and Leadership: Journey Towards Equity. Grounded in leadership theory and research, this text delves into the barriers and challenges women face on their leadership journeys, including stereotypes, bias, inequality, discrimination, and domestic responsibilities. The text includes several chapters devoted to strategies and tools for overcoming obstacles, creating structural change, and moving towards greater equity.
Core Textbook.
Includes bibliographical references.
Keywords: elektronické knihy; electronic books; Business and Management -- Business and Management -- Education